Communicating with power in a volatile, uncertain, complex, and ambiguous world - Ang, Peng Hwa (2019)
In some ways this is the best of times: we have not had a world war, and overall we are living longer and healthier lives. In some ways, this is perhaps the most uncertain of times, more than at any other time in our living memory. Countries are more inward-looking and less inclusive; the media, the institution that is critical both for democracy and our discipline, is under attack; and so is our identity as researchers of truth, as facticity is questioned. This address makes the case that we have much to contribute as researchers, because good research aims to make the world a better place.